Effects of Leaf Pruning and Nitrogen Fertilizer Application on the Growth and Yield of Sweet Corn (Zea mays saccharata Sturt) - Riska Widiya Puteri; Didik Utomo Pribadi; Agus Sulistyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Sweet corn production in Indonesia is relatively low due to instability and many factors, including infestation of pests and diseases, inappropriate and inefficient cultivation techniques, and the varieties. Pruning the leaves below the cob and applying nitrogen fertilizer may improve yield. The aim of this research was to investigate the combined effect of leaf pruning and types of nitrogen fertilizer on the growth and yield of sweet corn plants. A plot experiment was performed in a Randomized Block Design with 2 factors, namely leaf pruning (no pruning, 1 leaf remaining, 2 leaves remaining, and 3 leaves remaining below the cob), and types of N fertilizer (Urea 4.5 g/plant, ZA fertilizer 9.6 g/plant, and KNO3 fertilizer 15.5 g/plant). Results showed that the best type of N source was KNO3 fertilizer with fresh weight of dehusked cobs (217.68 g), cob diameter (44.84mm), and sugar content (16.26%). Combination treatment of KNO3 fertilizer and the 3 leaves remaining provided the best results on the parameters of fresh weight of husked cobs (308.50 g), cob length (18.83 cm), weight of husked cobs (10.12 kg/plot), and yield of husked cobs (28.11 ton/ha). Keywords: Cultivation, Fertilizer, Nitrogen, Productivity, Sweet corn.